2011
DOI: 10.1021/jp200405y
|View full text |Cite
|
Sign up to set email alerts
|

Valence State and Catalytic Role of Cobalt Ions in Cobalt TiO2 Nanoparticle Photocatalysts for Acetaldehyde Degradation under Visible Light

Abstract: CobaltÀcarbonÀsulfur-codoped anatase photocatalysts (size <9 nm) were synthesized by hydrolyzing titanium(IV) isopropoxide in the presence of cobalt salts and ammonium thiocyanate at room temperature. The annealed photocatalysts were characterized with nitrogen adsorp-tionÀdesorption isotherms, energy-dispersive X-ray (EDX), X-ray diffraction (XRD), UVÀvisible diffuse reflectance, transmission electron microscopy (TEM), X-ray photon spectroscopy (XPS), and photoluminescence (PL) measurements. Characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…The CoTiO 2 samples show varied bandgap depending on the cobalt loading (Table 1). Previous research on Co-TiO 2 has shown that the bandgap varies as function of cobalt loading [14]. The bandgaps were calculated by extrapolation of the high slope region in the DRS plot to the X-axis and was found to be 3.01 eV for the non-modified titania sample and between 2.31 and 2.62 eV for the Co-modified sample.…”
Section: Diffuse Reflectance Spectroscopic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CoTiO 2 samples show varied bandgap depending on the cobalt loading (Table 1). Previous research on Co-TiO 2 has shown that the bandgap varies as function of cobalt loading [14]. The bandgaps were calculated by extrapolation of the high slope region in the DRS plot to the X-axis and was found to be 3.01 eV for the non-modified titania sample and between 2.31 and 2.62 eV for the Co-modified sample.…”
Section: Diffuse Reflectance Spectroscopic Studiesmentioning
confidence: 99%
“…Efforts to extend the response of titania based semiconductors into the visible region include coupling it with other low band gap semiconductors such as CdS, doping with metals, and/or non-metals and modification of its surface [11e15]. Among these, doping or surface modification of titania with transition metal ions has been studied for a variety of photocatalytic reactions such as CCl 4 dechlorination [11], reduction of nitrite and nitrate ions [16], acetaldehyde degradation [14,17], degradation of aromatic organics [18e21], and degradation of dyes [12,22e26]. However, contradictory reports exist in literature regarding the effect of doping due to variations in the location, nature, content, d electronic configuration of the dopant ions, diffusion length of the minority carriers, and the effectiveness of the dopant ions in trapping electrons and/or holes [11,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 schematically shows the co-doped structure and the coupling mechanism. There are ongoing attempts to codope cation dopant with the mentioned anions for increasing the efficiencies of photochemical reactions, such as Co-C-S [161] and Fe-N [162], yet, theoretical studies of these complex co-doping schemes are limited. Furthermore, owing to the complex nature of photochemical reactions, the dopant can affect the surface texture and the reaction pathway [150,157,161], all of which complicate theoretical studies.…”
Section: Double-hole Doping Of Tiomentioning
confidence: 99%
“…A variety of metals on TiO 2 have been explored, including Fe, Cr, V, Ni, Nb, Mn, Cu, Al, Bi, and Co, and the references provided are for the best representative examples. [29][30][31][32][33][34][35][36][37][38][39] In most of these cases, publications have shown that cation doping of TiO 2 results in products that easily show visible light absorptivity; however, in general this does translate into photoactivity. However, having stated this, there have been some successful reports such as the one by Iino and coworkers where they have shown that cation doping (using Cr 3+ ) of TiO 2 results in both visible light absorptivity and photoactivity toward NO.…”
Section: Doping the Semi-conducting Oxides To Form States That Can Abmentioning
confidence: 99%